2014
DOI: 10.1111/gtc.12128
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of LUBAC‐mediated linear ubiquitination by a specific interaction between LUBAC and the deubiquitinases CYLD and OTULIN

Abstract: Linear ubiquitin chains generated by the linear ubiquitin chain assembly complex (LUBAC) play an important role in NF-jB activation. However, the regulation of linear ubiquitin chain generation by LUBAC is not well characterized. Here, we identified two deubiquitinating enzymes (DUBs), ovarian tumor DUB with linear linkage specificity (OTULIN/Gumby/ FAM105B) and cylindromatosis (CYLD) that can cleave linear polyubiquitin chains and interact with LUBAC via the N-terminal PNGase/UBA or UBX (PUB) domain of HOIP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
136
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(146 citation statements)
references
References 55 publications
(179 reference statements)
10
136
0
Order By: Relevance
“…In contrast, USP10 was able to disassemble the Lys-63-linked chain by cleaving the individual ubiquitin moiety (21). Another well characterized DUB, CYLD, was also found to cleave both the Lys-63 chain and linear chain in vitro (43) and form a complex with OTULIN to suppress linear ubiquitination in cells (44). We found that overexpression of CYLD or OTULIN diminished NEMO linear ubiquiti- nation by genotoxic stress, whereas deletion of TANK had little impact on CYLD/OTULIN-dependent deubiquitination of NEMO (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, USP10 was able to disassemble the Lys-63-linked chain by cleaving the individual ubiquitin moiety (21). Another well characterized DUB, CYLD, was also found to cleave both the Lys-63 chain and linear chain in vitro (43) and form a complex with OTULIN to suppress linear ubiquitination in cells (44). We found that overexpression of CYLD or OTULIN diminished NEMO linear ubiquiti- nation by genotoxic stress, whereas deletion of TANK had little impact on CYLD/OTULIN-dependent deubiquitination of NEMO (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Three PUB-domain containing proteins have been described so far in humans and all interact with the p97 C-terminal tail: PNGase (peptide N-glycanase) [85,86], which is involved in the deglycosylation of misfolded glycoproteins [87], the UBX protein UBXD1 [68,85,88], and HOIP (HOIL-1-interacting protein) [89][90][91], the catalytic subunit of the E3 ubiquitin ligase LUBAC, which catalyzes the assembly of linear ubiquitin chains [92]. Molecular insights into the interaction of the PUB domain with p97 were revealed by crystal structures of the PNGase and HOIP PUB domains in complex with peptides comprising the five and four, respectively, C-terminal residues of p97 called PIM (PUB Interacting Motif) [86,91] (Fig.…”
Section: The Pub Domainmentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation